Healthy days at home and prognosis of older adults with cancer and non-cancer serious life-limiting illnesses - Oluwaseun J. Adeyemi; Nina Siman; Allison M. Cuthel; Keith S. Goldfeld; Corita R. Grudzen (BMC Geriatrics)
Abstract Background Healthy Days at Home (HDaH) is a patient-centered outcome measure quantifying the number of days individuals spend at home without hospitalizations or emergency department (ED) visits, while maintaining functional independence. This study examines the association between HDaH and prognosis among US older adults with serious life-limiting illnesses (commonly heart failure, chronic obstructive pulmonary disease, advanced cancer, and end-stage kidney disease) and explores how this relationship differs by cancer status. Methods For this prospective cohort design study, we pooled Medicare Claims data of older adults (aged 66 or greater) with serious life-limiting illnesses who visited one of 30 EDs participating in the Primary Palliative Care for Emergency Medicine study between 2015 and 2019. The main exposure was prognosis, measured using the Gagne index, a short-term predictor of mortality. We controlled for age, sex, race/ethnicity, and used cancer diagnosis as a secondary predictor and stratification variable. The outcome, HDaH, was defined as 180 days minus the days a patient spent in healthcare institutions, including hospitals, skilled nursing facilities, and hospice care. We used generalized linear mixed-effects models with a log (180) offset to estimate the adjusted rate ratios (aRR) and 95% confidence intervals. Results The cohort included 122,579 seriously ill older adults,11% (n = 13,452) of whom had cancer. The median (IQR) HDaH was 115 (26–174) days. Each unit increase in Gagne index score was associated with a 6.0% decrease in the rate of HDaH (aRR: 0.94; 95% CI: 0.94 to 0.94), a pattern observed in both cancer and non-cancer groups. Cancer diagnosis was associated with 7.0% increase in HDaH (aRR: 1.07; 95% CI: 1.07 to 1.07). Conclusion While poor prognosis is associated with fewer healthy days at home, cancer diagnosis is associated with more healthy days at home. Our findings highlight the need for tailored care models to reduce hospitalizations and increase HDaH for patients with serious life-limiting illnesses other than cancer.